The ancestry and affiliations of Kennewick Man - Rasmussen, Morten; Sikora, Martin; Albrechtsen, Anders; Korneliussen, Thorfinn Sand; Moreno-Mayar, J. Víctor; Poznik, G. David; Zollikofer, Christoph P. E.; Ponce de León, Marcia S.; Allentoft, Morten E.; Moltke, Ida; Jónsson, Hákon; Valdiosera, Cristina; et al. (Nature (London), 2015)
Kennewick Man, a 8,500-year-old male human skeleton discovered in Washington state, USA, has been the subject of scientific and legal controversy; here a DNA analysis shows that Kennewick Man is closer to modern Native Americans than to any other extant population worldwide. Who was Kennewick Man? Kennewick Man is a 9,000-year-old male human skeleton discovered in Washington state, USA in 1996. The population affinities of the remains have been the subject of scientific and legal controversy. Initial studies based on morphology suggested that the skeleton was not of Native American affinity. Eske Willerslev and colleagues now present DNA analysis showing that Kennewick Man is in fact closer to modern Native Americans than to any other extant population worldwide. Kennewick Man, referred to as the Ancient One by Native Americans, is a male human skeleton discovered in Washington state (USA) in 1996 and initially radiocarbon dated to 8,340–9,200 calibrated years before present ( bp ) 1 . His population affinities have been the subject of scientific debate and legal controversy. Based on an initial study of cranial morphology it was asserted that Kennewick Man was neither Native American nor closely related to the claimant Plateau tribes of the Pacific Northwest, who claimed ancestral relationship and requested repatriation under the Native American Graves Protection and Repatriation Act (NAGPRA). The morphological analysis was important to judicial decisions that Kennewick Man was not Native American and that therefore NAGPRA did not apply. Instead of repatriation, additional studies of the remains were permitted 2 . Subsequent craniometric analysis affirmed Kennewick Man to be more closely related to circumpacific groups such as the Ainu and Polynesians than he is to modern Native Americans 2 . In order to resolve Kennewick Man’s ancestry and affiliations, we have sequenced his genome to ∼1× coverage and compared it to worldwide genomic data including for the Ainu and Polynesians. We find that Kennewick Man is closer to modern Native Americans than to any other population worldwide. Among the Native American groups for whom genome-wide data are available for comparison, several seem to be descended from a population closely related to that of Kennewick Man, including the Confederated Tribes of the Colville Reservation (Colville), one of the five tribes claiming Kennewick Man. We revisit the cranial analyses and find that, as opposed to genome-wide comparisons, it is not possible on that basis to affiliate Kennewick Man to specific contemporary groups. We therefore conclude based on genetic comparisons that Kennewick Man shows continuity with Native North Americans over at least the last eight millennia.